Social Media and the Shortcut Blade for Justice Seekers (Open Society Conference, 2023)
The existence of social media has changed the structure of people's lives, becoming a necessity for people in the digital world. This age is open without time and place restrictions. The aim of this article is to highlight this phenomenon and explore how social media can act as an instrument of justice and law enforcement. The method used in this work follows the rules of literary research. In addition, the discussion in this journal is as follows: (1) The use of social media in public can bring many advantages, but also disadvantages. This can especially affect the law and the judiciary; and (2) Law enforcement officials, as well as police investigators, prosecutors, judges and advocates, in enforcing the law, especially in legal matters, have caused considerable anxiety in the community. Therefore, it is necessary to strengthen the court institution as a place that presents an atmosphere and a sense of peace for justice seekers, so that the main task of the court in carrying out justice and peace among the people is not as desired.